Influence of the gas pressure in a Torr regime capacitively coupled plasma deposition reactor. (2nd June 2021) - Kim, Ho Jun
Abstract: The adjustment of the gas pressure has been shown to improve the deposition rate and uniformity of a plasma process. This led us to investigate the effect of the gas pressure in a 300 mm wafer reactor. We numerically simulated SiH4 /He capacitively coupled plasma discharges for the deposition of a hydrogenated amorphous silicon film. The results indicated that an increase in the gas pressure leads to uniform dissipation of the power coupled to the plasma and deposition profiles. By toggling the sidewall condition from grounded to dielectric while varying the gas pressure, we observed a modification of the plasma distributions and deposition profiles. Based thereupon, we concluded that the combination of high pressure with narrow electrode spacing can guarantee more efficient and uniform deposition. Additionally, this result was experimentally validated using the plasma deposition of hydrogenated amorphous carbon from the mixture C3 H6 /Ar/He. Even though the mixture differed from that we adopted in the simulation, the combination of high pressure with narrow electrode spacing still induced uniform deposition.